Chemo-Selective Protection of Aldehydes Functional Group Catalyzed by MOFs - Sakineh Mahdian; Leila Panahi; Mohammad Reza Naimi-Jamal (Chemistry Proceedings, 2022)
A metal-organic framework Zn2(BDC)2(DABCO) was employed as a reusable heterogeneous acidic catalyst in the acylation reaction of various benzaldehydes with acetic anhydride under microwave irradiation. The outstanding features of this efficient solvent-free method are short reaction time, ease of product separation, greatest yields, and the ability to reuse the catalyst several times.